PENGARUH MEDIA PEMBELAJARAN POP-UP BOOK TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK PADA DEEP LEARNING PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Shella Priscillia; Rabiyatul Adawiyah Siregar; Deviyanti pangestu; Sowiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of pop-up book learning media on students’ creative thinking ability in the deep learning approach of IPAS subject for fourth-grade students at SDN 1 Purwodadi Dalam. This study used a quantitative quasi-experimental method with a non-equivalent control group design. The sample consisted of 53 students 27 in the experimental class (IV B) and 26 in the control class (IV A). Data were collected through essay tests measuring four creative thinking indicators: fluency, flexibility, originality, and elaboration. Simple linear regression showed a significance value of 0.000 < 0.05, R Square = 0.783, meaning pop-up book media contributed 78.3% to creative thinking ability. N-Gain of the experimental class (0.61) was higher than the control class (0.35), and the posttest mean of the experimental class (74.11) exceeded the control class (59.31). Media implementation reached 73% (active category). Pop-up book learning media significantly affects the creative thinking ability of fourth-grade students in the IPAS deep learning approach.